Get a Copy Find a copy in the library AbeBooks$3.95 Amazon$978.00 Better World Books$23.57 A night on the Orient Express - Veronica Henry (Orion, 2013)
It's a frosty night in November as a group of passengers climb aboard the Orient Express for the journey of a lifetime from London to Venice. As they settle into the luxury of their cabins and take their first sips of champagne, they all have different hopes and expectations. Some have waited a lifetime for the experience, for others, it is a surprise; for many, a celebration. One thing is certain, the journey won't